Household resilience to drought: The case of Salima District in Malawi - Banda, Taonga F.; Phiri, M.A.R.; Mapemba, L.D.; Maonga, Beston B. (International Food Policy Research Institute, 2016)
This study identifies factors that affect resilience to drought among smallholder farmers in Salima, one of the districts frequently affected by drought in Malawi. The study contributes to the existing literature by constructing a drought resilience index (DRI) and uses it to determine the effect of drought resilience on the welfare of farming households. Principal Com-ponents Analysis (PCA) is used to construct the DRI. Appreciating that smallholder farmers actively respond to events that threaten their livelihoods, the study identified how factors such as household assets, social capital, the size of land held by the farming household, and others factors help farmers to absorb adverse welfare effects resulting from prolonged dry spells and droughts. In order to capture the effect of drought on the welfare of farming households, a stochastic frontier production function is estimated. Results suggest that over 62 percent of households in the study area were not resilient and, hence, vulnerable to the adverse effects of dry spells. Factors such as age of the household head, size of the farm family, landholding size, and the number of immediate family members living outside the household are identified as af-fecting the drought resilience of farming households. The study also finds a positive correlation between resilience and improved household welfare. The policy implications from the results of this study include promoting productivity enhancing technologies, diversifying crop production from maize, and pursuing household livelihoods outside of agriculture in order to reduce the risks to household welfare resulting from drought.